Endotyping Seasonal Allergic Rhinitis in Children: A Cluster Analysis - Malizia, Velia; Ferrante, Giuliana; Cilluffo, Giovanna; Gagliardo, Rosalia; Landi, Massimo; Montalbano, Laura; Fasola, Salvatore; Profita, Mirella; Licari, Amelia; Marseglia, Gian Luigi; La Grutta, Stefania (Frontiers in Medicine, 2022)
Background Seasonal Allergic Rhinitis (SAR) is a heterogeneous inflammatory disease. We hypothesized that a cluster analysis based on the evaluation of cytokines in nasal lavage (NL) could characterize distinctive SAR endotypes in children. Methods This cross-sectional study enrolled 88 children with SAR. Detailed medical history was obtained by well-trained physicians. Quality of life and sleep quality were assessed through standardized questionnaires [Pediatric Rhinoconjunctivitis Quality of Life Questionnaire (PRQLQ) and Pittsburgh Sleep Quality Index (PSQI) respectively]. Children were grouped through K-means clustering using Interleukin (IL)-5, IL-17, IL-23, and Interferon (INF)-γ in NL. Results Out of the 88 patients enrolled, 80 were included in the cluster analysis, which revealed three SAR endotypes. Cluster 1 showed lower levels of IL-5 and IL-17 and intermediate levels of IL-23 and IFN-γ; Cluster 2 had higher levels of IL-5 and intermediate levels of IL-17, IL-23, and IFN-γ; Cluster 3 showed higher levels of IL-17, IL-23, and IFN-γ and intermediate levels of IL-5. Cluster 1 showed intermediate values of nasal pH and nasal nitric oxide (nNO), and a lower percentage of neutrophils at nasal cytology than Clusters 2 and 3. Cluster 2 had a lower level of nasal pH, a higher nNO, higher scores in the ocular domain of PRQLQ, and worse sleep quality than Clusters 1 and 3. Cluster 3 showed a higher percentage of neutrophils at nasal cytology than Clusters 1 and 2. Conclusions Our study identified three endotypes based on the evaluation of cytokines in NL, highlighting that childhood SAR is characterized by heterogeneous inflammatory cytokines.